Valorization of Plastic Wastes for the Synthesis of Imidazolium‐Based Self‐Supported Elastomeric Ionenes. Issue 12 (25th May 2020) - Demarteau, Jeremy; O'Harra, Kathryn E.; Bara, Jason E.; Sardon, Haritz
Abstract: Imidazolium‐based ionenes are known to be high‐performance materials for a great variety of applications. The preparation of these polymers requires the use of bis‐imidazole starting monomers, which are commonly prepared by using toxic chloride reagents. In this study, bis‐imidazole monomers are synthesized by organocatalytic chemical recycling of discarded plastics through chemical depolymerization. By using poly(ethylene terephthalate) and bisphenol A polycarbonate as starting materials, different monomers containing amide or urea functionalities are prepared to produce high‐molecular‐weight ionic polymers. These novel ionenes show excellent elastomeric and self‐healing behavior, serving as a promising means to expand the exploration of plastic wastes as a source of new materials. Abstract : Any old ionene : Smart chemical recycling of plastic wastes is key to accessing more sustainable production. Two major plastic wastes—poly(ethylene terephthalate) and bisphenol A polycarbonate—are efficiently depolymerized by using imidazole–amine derivatives and an organocatalyst. The resulting synthons are used for the formation of self‐supported, high‐molecular‐weight imidazolium ionenes, which exhibit elastomeric behavior and self‐healing properties.